Defeitos congênitos e exposição a agrotóxicos no Vale do São Francisco - Silva, Silvio Romero Gonçalves e [UNIFESP] (2010)
Objective: To evaluate associations between genitor exposure to pesticides and births with congenital defects in the São Francisco Valley, as well as the demographic profile and the defects found. Methods: In this case-control study, each case (newborns with congenital defects) had two controls (healthy newborns). The subjects were born at the São Francisco Valley, in 2009. The sample consisted of 42 cases and 84 controls. Data were gathered using a structured questionnaire adapted from Latin American Collaborative Study of Congenital Malformations (ECLAMC), with the addition of questions relating to exposure to pesticides; and from analysis on the medical files and contact with the hospital’s pediatricians. X2 test was performed with a significance level of 5% to identify the variables with the greatest differences between case and control groups. Odds ratios (ORs) for the sample were then calculated, along with ORs from logistic regression analysis; and finally, multivariate logistic regression analysis was performed. Results: Newborns with congenital defects were more associated with genitor exposure to pesticides, in comparison with healthy newborns, but without statistical significance. Greater risk was observed when all types of exposure were considered (adjusted OR: 1.33; 95% CI = 0.45- 3.91). The sociodemographic variables with significant differences between the groups were: low schooling level, low weight, prematurity, young genitors, chronic diseases and physical factors. Multiple malformations and defects of the musculoskeletal and nervous systems were more frequently found. Conclusions: The present study showed association between exposure to pesticides and occurrences of congenital defects. However, without statistical significance.